Translating “Lunokhod”: Textual Order, Chaos and Relevance Theory - Bullock, Mercedes (Université d'Ottawa / University of Ottawa, 2020)
This thesis examines the concepts of textual order and chaos, and how Relevance Theory can be used to translate texts that do not adhere to conventional textual practices. Relevance Theory operates on the basis of presumed order in communication. Applying it to disordered communicative acts provides an opportunity and vocabulary to describe how communication can break down, and the consequences this can have for translation. This breakdown of order, which I am terming a ‘chaos principle’, will be examined through the lens of a Russian-language short story called “Lunokhod”, a story in which textual order, as described by Relevance Theory, breaks down. In this thesis, I first lay out several translation challenges presented by my corpus, discuss each with reference to Relevance Theory, and examine the implications for translation through sample translation segments. This deconstruction section argues that conventional translation methods fail to properly address the challenges of my corpus. Next comes a reconstruction section, in which I develop a theoretical framework for my translation that has roots in Relevance Theory but that frees the translation from the constraints imposed by an ordered view of communication. Finally, I present the translation itself.
Keywords: Translation; Translation Studies; Relevance Theory; Russian; Russian Literature; Viktor Pelevin; Surrealism; Text Reception; Cognition; Chaos Theory